Therapeutic abandonment in multidrug-resistant tuberculosis: Associated factors in a high burden region in Perú - Rivera, Orianda (2019)
Introduction: In the approach of multidrug-resistant tuberculosis, the therapeutic abandonment constitutes a serious problem of public health, affecting the quality of life of patients, families and community. Addressing it poses a burden on health systems, because it causes free sources of transmission in the community, and increases in prevalence and mortality. Hence the need to investigate those factors associated with this situation. Objective: To identify risk factors associated with treatment default in patients with multidrug-resistant tuberculosis in the Callao-Peru region. Materials and methods: Analytical case-control study (cases = 80 and controls = 180) that started treatment from January 01, 2010 to December 31, 2012. The factors were identified by logistic regression, calculating the odds ratios (OR) and 95% confidence intervals. Results: Finding risk factors in the multivariate analysis: Not having knowledge of the disease, OR aj = 23.10 [95% CI, 3.6-36.79; (p .002)], Do not believe in healing, OR aj = 117.34 [95% CI 13.57-124.6; (p .000)]; Not having social support, OR aj = 19.16 [95% CI 1.32-27.77; (p .030)]; Do not consider adequate working hours, OR aj = 78.13 [IC95% 4.84-125.97; (p .002)]; Do not receive laboratory reports, OR aj = 46.13 [95% CI 2.85-74.77; (p .007)] Conclusions: Health services should direct efforts for the early identification of conditions that could become risk factors, which would help preventively implement effective, rapid and high-impact interventions. © 2019 Instituto Nacional de Salud.